Characterization of the Degradation of Sheepskin by Monitoring Cytochrome c of Bacteria by Raman Spectroscopy. (13th April 2021) - Mehta, Megha; Liu, Yang; Waterland, Mark; Holmes, Geoff
Abstract: To probe the bacterial growth on animal skin, there is a need for a rapid, reliable, and sensitive method that is able shed light on the mechanism by which bacteria grow under different environmental conditions. Raman spectroscopy provides information about the changes in the molecular structure of skin through rapid and continuous monitoring of the growth of bacteria. In this study, sheepskin inoculated with and without Aeromonas hydrophilia bacteria followed by storage at 4 °C for 10 days was investigated using Raman spectroscopy. Using the resonance Raman of cytochrome c found in Aeromonas hydrophilia, the alterations in the biochemistry of sheepskin upon bacterial growth was studied. A detailed analysis of spectra reveals that bacterial cytochrome c band at 747 cm −1 increased by 72.3% and another prominent cytochrome c marker band at 1582 cm −1 increased by 70.6% from day 3 to day 7. The changes in the Raman band area of biomolecules such as proteins, lipids, and cytochrome c were measured and reported using ratiometric analysis of four novel ratiometric markers (I747 /1646, I1445 /1646, I1581 /1646, I1618 /I1646 ). Curve-fitting by the sum-of-Gaussians method was carried out on the amide I band at 1646 cm −1 to investigate the secondary structures responsible for alterations in the collagen network for a period of 10 days. Multivariate analysis methods such as principal component analysis also supported the ratiometric markers of bacterial growth. Altogether the findings obtained highlight the potential of Raman spectroscopy, in combination with multivariate analysis, for the identification of universal biochemical signatures indicative of bacterial growth on sheepskin. This study opens the possibility for the development of preservation methods for the prevention of bacterial degradation in skins stored in a refrigerator at an optimum temperature of 4 °C.